Systemic RNA interference (RNAi) therapeutics for the treatment of HIV-1 - Rossi, John (Henry Stewart Talks, 2014)
Systemic RNA interference (RNAi): Therapeutics for the treatment of HIV-1, HIV life cycle, Typical Course of HIV infection, Why do we need new HIV drugs?, Major goals of anti-HIV therapies, Combinatorial RNA based therapy for HIV, Applying RNAi for the treatment of human diseases, treat HIV infection by systemic delivery of small RNAs, Aptamers, Chimeric-siRNA aptamer uptake into gp120 expressing cells, Aptamer-targeted RNA interference for HIV-1 therapy, Aptamer and aptamer chimera mediated inhibition of HIV-1, Small animal model for studying anti-HIV RNAi based therapies, Both aptamer and aptamer chimera inhibit HIV infection -Aptamer and chimeric aptamer-siRNA prevent CD4+ cell decline, Aptamer and dsiRNAS effect on viral load, Flexible PAMAM dendrimers with a triethanolamine core, Dendrimers plus siRNAs form nanoparticles, protect siRNA from degradation and deliver siRNAs to T-lymphocytes, G5 dendrimer delivered siRNAs down regulate target mRNAs in vitro, Multiplex siRNAs for HIV-1 treatment, In vivo analyses of G5 dendrimer delivered siRNAs, Reductions in HIV loads following dendrimer siRNA injections, Dendrimer-siRNA complexes protect HIV infected RAG-hu mice from CD4 T cell loss, Bio distribution of G5 dendrimer siRNAs
Reviewed at 2020/07/16